THE ROLE OF EMOTIONAL INTELLIGENCE IN LEADERSHIP EFFECTIVENESS - Zunsyika Zahra Zatira; Sugiharti; Janna Prafika; Nurul Wijayanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Modern corporate organizations acknowledge that emotional intelligence (EI) is among the most critical factors in leadership effectiveness. Leaders who score high in EI are better able to implement supportive work environments, and this then puts them on the path to improved job satisfaction and organizational commitment. Besides, the effectiveness of EI for the purpose of diversity management and inclusive cultures underscores the value leaders with highly developed EI have in today's work settings, which are characterized by increased globalization. The ongoing challenges of integrating EI into leadership development programs necessitate further exploration. This paper, therefore, synthesizes the latest findings, arguing for the importance of EI in modern leadership and suggesting a more nuanced inclusion of emotional competencies in leadership strategies, so as to be able to effectively navigate the complex dynamics of modern organizations. Keywords: Emotional Intelligence, Leadership Effectiveness, Organizational Culture, Diversity Management, Change Management.